Analisis Tingkat Erosi pada Sungai Konaweha di Kabupaten Konawe - Sakti, Putra (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2021)
Erosion causes the loss of a fertile layer of soil and good for crop growth as well as reduced soil ability to absorb and retain water. The transported land will be deposited elsewhere, in rivers, reservoirs, lakes, irrigation channels, on farmland and so on. The purpose of this research is to analyze the large rainfall of the Konaweha River area. Analyzes large actual erosion (EA) & Potential Erosion (Ep), the average that occurs on the Konaweha River every year.The method used to calculate average maximum rainfall is arithmetic.Based on the results of analysis gained on erosion at the upper Abuki River, the location in Konawe district, can be concluded as follows:So the magnitude of actual erosion (Ea) on average that occurs on the river Konaweha every year coming 5.829 tons/ha/year, and potential erosion (Ep) on average that occurs on the river Konaweha every year coming 196.246 tons/ha/year.